2011
DOI: 10.1177/0194599811416318a21
|View full text |Cite
|
Sign up to set email alerts
|

Free Flap Reconstruction of Lateral Mandibular Defects: Indications and Outcomes

Abstract: Objective-To compare outcomes following osteocutaneous radial forearm and fibula free flap reconstruction of lateral mandibular defects.Study Design-Retrospective case controlled study. Setting-Two academic tertiary care centers.Subjects and Methods-Patients who underwent free flap reconstruction of lateral mandibular defects from 1999 to 2010 were classified into four groups based on type of reconstruction: 1) radial forearm swing (n = 8), 2) radial forearm with bar (n = 5), 3) osteocutaneous radial forearm (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
47
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(50 citation statements)
references
References 9 publications
2
47
1
Order By: Relevance
“…24 Some authors report donor site complications in the radial osteocutaneous flap at a rate of 0% to 7%, none of which are fractures. 21,23,25 These rates increase in other studies to 28% to 30% when tendon exposure is included. 23,26 In these studies, the need for surgical revision of the donor site is still low at 0% to 7%.…”
Section: Discussionmentioning
confidence: 77%
“…24 Some authors report donor site complications in the radial osteocutaneous flap at a rate of 0% to 7%, none of which are fractures. 21,23,25 These rates increase in other studies to 28% to 30% when tendon exposure is included. 23,26 In these studies, the need for surgical revision of the donor site is still low at 0% to 7%.…”
Section: Discussionmentioning
confidence: 77%
“…Deficiencies in soft tissue coverage may be an important factor in the development of plate extrusion. Several authors have noted that hardware exposure occurred at a higher rate in patients who underwent osseocutaneous radial forearm free flaps (OCRFFF) versus fibular free flaps (FFF), and concluded that this was likely due to the smaller amount of soft tissue incorporated in the OCRFFF (Day et al, ; Dean et al, ; Virgin et al, ). The subscapular system of free flaps makes available considerable soft tissue bulk with excellent mobility of the soft tissue relative to the bony component and generally provides abundant soft tissue coverage of the reconstruction plate (Gibber et al, ; Urken et al, ; Yoo et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The results show that these flaps are similar with respect to complications and provide equivalent functional outcomes (7,8). Interestingly, despite evidence suggesting the OC-RFFF cannot support dental implants (18), both studies reported more patients in the OC-RFFF group receiving implants than in the fibula group (7,8). Dental implants typically require the addition of supplemental bone graft in the case of the OC-RFFF or fubula.…”
Section: Discussionmentioning
confidence: 89%
“…The rate of fracture when all patients undergo PIF was 0.5% in two large retrospective reviews (3,9), and 0% (25,26) to 9.6% in smaller similar series (5,27). Routine PIF appears to have reduced the fracture risk associated with the OC-RFFF, even in the setting of large bone flaps (harvest of 40% to 50% of the radius circumference) (3,7,25). Because this is a new modification, there are no data regarding the effect of including the border of the radial styloid on fracture risk, although we suspect it will not affect the fracture rate because invariably, the fracture occurs proximally where the radius is the narrowest.…”
Section: Discussionmentioning
confidence: 98%